Investigation of drug release from thermo- and pH-sensitive poly(N-isopropylacrylamide/itaconic acid) copolymeric hydrogels - KAYAMAN APOHAN, NİLHAN (JOHN WILEY & SONS LTD, 2004)
N-Isopropylacrylamide/itaconic acid copolymeric hydrogels were prepared by irradiation of the ternary mixtures of N-isopropylacrylamide/itaconic acid/water by gamma-rays at ambient temperature. The dependence of swelling properties and phase transitions on the comonomer concentration and temperature were investigated. The hydrogels showed both temperature and pH responses. The effect of comonomer concentration on the uptake and release behavior of the hydrogels was studied. Methylene blue (MB) was used as a model drug for the investigation of drug uptake and release behavior of the hydrogels. The release studies showed that the basic parameters affecting the drug release behavior of the hydrogels were pH and temperature of the solution. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: hydrogels; poly(N-isopropylacrylamide/itaconic acid); methylene blue; drug delivery systems; swelling